ARTERIAL HYPERTENSION HIGH RISK GROUPS IN MODERN INTERPRETATION - Xolmatov Mexroj; Boltayev Xusan; Mardonqulov Akmal (Journal of Science in Medicine and Life, 2024)
Arterial hypertension is a syndrome of increased systolic and (or) diastolic blood pressure. To make such a diagnosis, the systolic level should be above 140 mmHg, and diastole should be above 90 mmHg. This condition is observed with repeated measurements, at different times of the day and under different conditions (rest, activity, waking up after sleep). Hypertension is also called hypertension or essential hypertension. The term "hypertension" was introduced in 1948 by the Soviet scientist GF Lang. Hypertension is one of the most common forms of arterial hypertension. According to statistics, about 30% of the adult population suffers from it, and the probability of developing the pathology increases over the years. With a sharp and significant increase in pressure, an attack called "hypertensive crisis" may occur. This is a dangerous condition that requires immediate medical attention, such as intravenous therapy.